THE IMPLEMENTATION OF MAQASHID SHARIAH IN ZAKAT INSTITUTION: COMPARISON BETWEEN INDONESIA AND MALAYSIA - Mustafida, Rifka; Kurnia, Zahra Nabila; Fauziah, Najim Nur; Subri, Nur Shazni Binti; Faiz, Farihah Amirah Binti Ahmad (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2020)
Zakat has been widely described as a tool of income distribution. Not with standing of the potential of zakat in Indonesia and Malaysia, however, there are some issues in zakat institutions. This study aims to analyze institutional program of collecting zakat in reaching Maqashid Sharia and also to identify the issues over the program conducted by the Selangor and DKI Zakat institutions. This study conducted a case study approach which involved two Zakat institutions in two different countries; Lembaga Zakat Selangor in Malaysia and Badan Amil Zakat Infaq and Sadaqah in Indonesia. Zakat Institution should be the leading institution in economic empowerment of society by using Maqashid Sharia as benchmark indicator to design zakat distribution program. This study found that LZS has fulfilled all aspects of maqashid ShariaSharia in zakat distribution program while BAZIS DKI meet three aspects of maqashid Sharia namely hifdzu ad-din, hifdzu an-nafs and hifdzu an-nasl. It is acknowledged that the zakat institutions have made many improvements, there are still few issues that need to be highlighted to meet the needs of the society. The following recommendations are given to empower and enhance the role of zakat particularly in accomplishing the objectives of the Sharia.